Studies on yield of two strains of Hypsizygus ulmarius (Bull.Fr) CO 2 and IIHR Hu 1 (Blue oyster mushroom) - Usha, S; Suguna, V (Mushroom Research, 2016)
Hypsizygus ulmarius is a popular mushroom due to its excellent consistency of cap and stipe, culinary qualities and longer shelf life. In Tamil Nadu, Hypsizygus ulmarius may be popularized among the consumers, but at present this mushroom is not cultivated commercially. In this study, two strains of Hypsizygus ulmarius CO (collected strain from TNAU, Coimbatore) and IIHR Hu 1 (collected strain from IIHR, Bangalore) were cultivated on paddy straw and their growth and yield parameters were investigated. Among the two strains tested, Hypsizygus ulmarius CO strain gave 51% biological efficiency. The mycelial run rate and number of fruit bodies were higher in Hypsizygus ulmarius CO strain. 2 2 than IIHR Hu 1